On a future transcendental account of probability in quantum mechanics - Pringe, Hernan Bruno (2013)
In this paper I put forward some ideas for a future transcendental account of probability in quantum mechanics. Such account will be based on the determination of the epistemological function that probabilistic laws play in quantum mechanics. By means of this determination I expect to take some steps toward a metaphysical foundation of quantum mechanics along Kantian lines, as well as to shed some new light on the current philosophical debate on the notion of probability in quantum mechanics.